Data Protection Laws in Indonesia: Navigating Privacy in the Digital Age - Prasetyo, Budi; Handayani, I Gusti Ayu Ketut Rachmi; Sulistiyono, Adi (Arbain Publishing, 2025)
The rapid expansion of digital technologies in Indonesia has brought significant challenges regarding data protection and privacy. With the increasing use of online services, e-commerce, and digital transactions, concerns over personal data security have intensified. In response, the Indonesian government enacted the Personal Data Protection Law (PDP Law) in 2022, marking a significant milestone in the country’s legal framework for data privacy. This study explores the implementation and effectiveness of data protection laws in Indonesia using a qualitative research approach. Through in-depth interviews with legal experts, government officials, and digital rights advocates, this research examines the extent to which current regulations align with global standards and whether they adequately address data security threats. The findings indicate that while the PDP Law represents progress, challenges remain in enforcement, compliance, and public awareness. Many organizations, particularly in the private sector, struggle to adapt to the new regulatory environment, and law enforcement agencies face difficulties in overseeing compliance due to resource limitations. Additionally, a lack of digital literacy among Indonesian citizens poses risks, as individuals are often unaware of their data protection rights. Comparisons with international best practices, such as the European General Data Protection Regulation (GDPR), reveal gaps in Indonesia’s approach, particularly in enforcement mechanisms and penalties for data breaches. This study highlights the need for greater government oversight, stronger institutional capacity, and enhanced public education programs to ensure that Indonesia’s data protection laws effectively safeguard digital privacy in the evolving digital landscape.